2019
DOI: 10.1186/s13075-019-1827-9
|View full text |Cite
|
Sign up to set email alerts
|

Tolerogenic XCR1+ dendritic cell population is dysregulated in HLA-B27 transgenic rat model of spondyloarthritis

Abstract: BackgroundSpondyloarthritis (SpA) is a chronic inflammatory disease affecting primarily axial and peripheral joints and sometimes also extra-articular organs, such as the gut. Rats transgenic for HLA-B27 and human β2-microglobulin (B27-Tg rat) develop clinical manifestations resembling human disease. In this model, it has been shown that CD103+ conventional dendritic cells (cDCs) exhibited altered functions, likely promoting SpA development. CD4− cDC subpopulation expressing XCR1, a chemokine receptor involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Looking in more details at cDC subpopulations, an imbalance was found between the cDC2 subset -implicated in T cell activation and cytokines production-and cDC1 -critical for tolerance induction-marked by a decreased proportion of the latter in the spleen, the mesenteric lymph nodes and the lymph draining the gut [29,36]. This could at least in part be related to the defective migration of cDC1 from the colonic mucosa to mesenteric lymph nodes, possibly due to cytoskeleton alteration [36].…”
Section: A-the Critical Implication Of Myeloid-derived Antigen-presenting Cells In Rat-spamentioning
confidence: 99%
See 2 more Smart Citations
“…Looking in more details at cDC subpopulations, an imbalance was found between the cDC2 subset -implicated in T cell activation and cytokines production-and cDC1 -critical for tolerance induction-marked by a decreased proportion of the latter in the spleen, the mesenteric lymph nodes and the lymph draining the gut [29,36]. This could at least in part be related to the defective migration of cDC1 from the colonic mucosa to mesenteric lymph nodes, possibly due to cytoskeleton alteration [36].…”
Section: A-the Critical Implication Of Myeloid-derived Antigen-presenting Cells In Rat-spamentioning
confidence: 99%
“…Looking in more details at cDC subpopulations, an imbalance was found between the cDC2 subset -implicated in T cell activation and cytokines production-and cDC1 -critical for tolerance induction-marked by a decreased proportion of the latter in the spleen, the mesenteric lymph nodes and the lymph draining the gut [29,36]. This could at least in part be related to the defective migration of cDC1 from the colonic mucosa to mesenteric lymph nodes, possibly due to cytoskeleton alteration [36]. Of particular interest was a relative decrease in all the organs studied and an altered capacity to support in vitro Treg differentiation, of the XCR1+ cDC1 subset, known to promote the induction of peripheral Treg by the production of transforming growth factor-β1 (TGF1) and retinoic acid from vitamin A [36,37].…”
Section: A-the Critical Implication Of Myeloid-derived Antigen-presenting Cells In Rat-spamentioning
confidence: 99%
See 1 more Smart Citation
“…The same study further showed that myeloid cells with a similar phenotype were found to be expanded in the SKG mouse model. In the HLA-B27-transgenic rat model of SpA, colonic tolerogenic (XCR1 + ) dendritic cells were reduced in HLA-B27-transgenic rats (as compared with control rats) and had a reduced capacity to induced T reg cell differentiation 166 . The results of these studies of myeloid cells should prompt in-depth phenotyping studies using next-generation technologies.…”
Section: Myeloid Cells Are Initiators Of Type 3 Immunitymentioning
confidence: 94%
“…AS's pathogenesis is multifactorial, involving multiple cell types, cellular processes, and molecular mediators and regulators [ 4 , 5 ]. Studies show that the major histocompatibility complex region (MHC) is closely related to AS, and about 95% AS patients are born with a gene named HLA-B27 [ 6 ]. However, HLA-B27 predisposition fails to fully explain the cause of the disease, and this leads to a strong effort to identify additional predisposing factors.…”
Section: Introductionmentioning
confidence: 99%